Husband’s knowledge, characteristics and participation in family planning - Suci Musvita Ayu; Liena Sofiana; Khafidhotul Amaliah (International Journal of Public Health Science (IJPHS), 2019)
Family planning is an attempt to measure the number and spacing of children. Thus, several ways or alternatives are taken to prevent or postpone pregnancy to Couple of Productive Age. The purpose of the study is to determine the relationship between husband’s knowledge and characteristics and their participation in Family Planning in Randusanga Kulon Village, Brebes District, Central Java. Observasional analytic study was conducted with Cross-sectional design, employed 94 respondents. Results of study revealed that there is a relationship between husbands’ knowledge and their participation in family planning. Similarly, there is also relationship between education and husband’s participation in family planning. However, there found no relationship between the number of children and husband's participation in family planning.